Reward System Realizes Teacher Job Satisfaction at An-Nahl Integrated Islamic High School, Jambi City - Mardayanti, Arlen; Samsu, Samsu; Badarussyamsi, Badarussyamsi; Fuadi, Afif (Dinasti Publisher, 2024)
This study aims to analyze in depth the